Cultural and biological properties of lumpy skin disease agent isolated in the Russian Federation in 2015 - A. V. Kononov; S. V. Kononova; I. N. Shumilova; A. A. Nesterov; A. V. Shishkov; V. I. Diyev; R. V. Yashin; A. V. Mischenko (Ветеринария сегодня)
The paper presents data on studied properties of lumpy skin disease virus adapted to goat gonad and lamb testicle cell cultures. Experimental infection of cattle with the obtained strain of lumpy skin disease virus induces systemic infection.